MicroRNAs as Potential Regulators of Immune Response Networks in Asthma and Chronic Obstructive Pulmonary Disease - Cañas, José A.; Rodrigo-Muñoz, José M.; Sastre, Beatriz; Gil-Martinez, Marta; Redondo, Natalia; del Pozo, Victoria (Frontiers in Immunology, 2021)
Chronic respiratory diseases (CRDs) are an important factor of morbidity and mortality, accounting for approximately 6% of total deaths worldwide. The main CRDs are asthma and chronic obstructive pulmonary disease (COPD). These complex diseases have different triggers including allergens, pollutants, tobacco smoke, and other risk factors. It is important to highlight that although CRDs are incurable, various forms of treatment improve shortness of breath and quality of life. The search for tools that can ensure accurate diagnosis and treatment is crucial. MicroRNAs (miRNAs) are small non-coding RNAs and have been described as promising diagnostic and therapeutic biomarkers for CRDs. They are implicated in multiple processes of asthma and COPD, regulating pathways associated with inflammation, thereby showing that miRNAs are critical regulators of the immune response. Indeed, miRNAs have been found to be deregulated in several biofluids (sputum, bronchoalveolar lavage, and serum) and in both structural lung and immune cells of patients in comparison to healthy subjects, showing their potential role as biomarkers. Also, miRNAs play a part in the development or termination of histopathological changes and comorbidities, revealing the complexity of miRNA regulation and opening up new treatment possibilities. Finally, miRNAs have been proposed as prognostic tools in response to both conventional and biologic treatments for asthma or COPD, and miRNA-based treatment has emerged as a potential approach for clinical intervention in these respiratory diseases; however, this field is still in development. The present review applies a systems biology approach to the understanding of miRNA regulatory networks in asthma and COPD, summarizing their roles in pathophysiology, diagnosis, and treatment.